2011
DOI: 10.3724/sp.j.1263.2011.00088
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment guidelines in the pharmacological management of chronic heart failure in an Australian population

Abstract: BackgroundTo document the pharmacotherapy of chronic heart failure (CHF) and to evaluate the adherence to treatment guidelines in Australian population.MethodsThe pharmacological management of 677 patients (female 46.7%, 75.5 ± 11.6 years) with CHF was retrospectively analyzed.ResultsThe use of angiotensin converting enzyme (ACE) inhibitors/angiotensin receptor blockers (ARB) and β-blockers were 58.2 % and 34.7 %, respectively. Major reasons for non-use of ACE inhibitors/ARBs were hyperkalemia and elevated ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…With our reported good adherence to ACEI/ARB, such patients would be eligible for additional BB and AA therapy [1,2,7,8] , although our data uncovered serious under-prescription of BB and AA classes. Consistently, wide variations in adherence have been reported for beta adrenergic blockers in CHF in other studies [12,15,[17][18][19][20] . In our study, adherence to BB (48%) was surprisingly higher than 34% reported for rural Australia, but much lower than 57.8% in Japan [14] and 84% for both USA [12] , and South Africa [20] .…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…With our reported good adherence to ACEI/ARB, such patients would be eligible for additional BB and AA therapy [1,2,7,8] , although our data uncovered serious under-prescription of BB and AA classes. Consistently, wide variations in adherence have been reported for beta adrenergic blockers in CHF in other studies [12,15,[17][18][19][20] . In our study, adherence to BB (48%) was surprisingly higher than 34% reported for rural Australia, but much lower than 57.8% in Japan [14] and 84% for both USA [12] , and South Africa [20] .…”
Section: Discussionsupporting
confidence: 61%
“…Thus, with regard to specific classes, the present study demonstrated a good physician -adherence of 83% for ACEI/ARB, which is comparable to those of South Africa, Europe and USA [12,15,17,20] . Interestingly, ours was higher than the ACEI/ARB adherence noted in Japan [14] , and rural Australia [19] . Other authors have suggested that class of physicians or seniority of physicians may influence level of knowledge and adherence [14][15][16] .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations